Utfodring av sällskapskanin. Vilka råd ger vi djurägarna? - Fridström, Therese (2014)
The most suitable method to answer the issues of this study was to do a combined literature- and questionnaire study. The literature part of the study was based on Original Research articles, Review Articles and books with a list of reference literature after each chapter and the purpose was to answer the questions “What feed items should be given to rabbits in different life stages” and “Which problems may develop from an inadequate diet?”